Removal of heavy metals in water using chitosan immobilized on sand - Rogel, Buenda D. (2008)
In recent years, biopolymers have been recognized as effective adsorbents for removal of metal ions in water. Among the biopolymers, chitosan has the highest capacity for adsorption of metal ions. Chitosan is derived from deacetylation of chitin, which found in exo-skeloton of shrimp, crab, some fungi and other crustaceans.